2017
DOI: 10.1021/acs.est.7b04197
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the Elementary Reaction Pathways of Criegee Intermediates to the Chemical Erosion of Squalene Interfaces during Ozonolysis

Abstract: Criegee intermediates (CI), formed in alkene ozonolysis, are central for controlling the multiphase chemistry of organic molecules in both indoor and outdoor environments. Here, we examine the heterogeneous ozonolysis of squalene, a key species in indoor air chemistry. Aerosol mass spectrometry is used to investigate how the ozone (O) concentration, relative humidity (RH), and particle size control reaction rates and mechanisms. Although the reaction rate is found to be independent of RH, the reaction products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
157
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(173 citation statements)
references
References 46 publications
(114 reference statements)
13
157
3
Order By: Relevance
“…These results indicate that the anti-conformer is substantially more reactive toward HO−CH 2 OO−H than syn-, dimethyl, and parent conformers in the atmosphere. A similar conclusion has been obtained by studying the reactions of synand anti-CH 3 CHOO with water and SO 2 ; i.e., the rate coefficient of the anti-CH 3 CHOO reaction was calculated to be 1 to 2 orders of magnitude higher than that of the syn-CH 3 CHOO system (Taatjes et al, 2013;Lin et al, 2016;Huang et al, 2015;Anglada and Solé, 2016). Therefore, it is concluded that the position and number of methyl groups significantly affect barrier heights and reaction rates.…”
Section: Pes Of Distinct Sci Reactions With Ho−ch 2 Oo−hsupporting
confidence: 78%
See 1 more Smart Citation
“…These results indicate that the anti-conformer is substantially more reactive toward HO−CH 2 OO−H than syn-, dimethyl, and parent conformers in the atmosphere. A similar conclusion has been obtained by studying the reactions of synand anti-CH 3 CHOO with water and SO 2 ; i.e., the rate coefficient of the anti-CH 3 CHOO reaction was calculated to be 1 to 2 orders of magnitude higher than that of the syn-CH 3 CHOO system (Taatjes et al, 2013;Lin et al, 2016;Huang et al, 2015;Anglada and Solé, 2016). Therefore, it is concluded that the position and number of methyl groups significantly affect barrier heights and reaction rates.…”
Section: Pes Of Distinct Sci Reactions With Ho−ch 2 Oo−hsupporting
confidence: 78%
“…The OH radical is one of the most powerful oxidants that participates in the atmospheric photochemical oxidation of VOCs (Gligorovski et al, 2015); it thus contributes to tropospheric ozone formation by being involved in the production of organic peroxy radicals (RO 2 ), which, in turn, facilitate the cycling of NO to NO 2 (Zhang and Zhan, 2002;Gligorovski et al, 2015). The remaining CIs become collisionally stabilized Criegee intermediates (SCIs) that can undergo further bimolecular reactions with a number of atmospheric trace gases, such as H 2 O, NO 2 , and SO 2 (Chen et al, 2016a(Chen et al, , b, 2018Mauldin et al, 2012;Berndt et al, 2014;Kuwata et al, 2015;Lin et al, 2016;Lin and Chao, 2017;Ouyang et al, 2013;Stone et al, 2014;Chao et al, 2015;Taatjes, 2017;Long et al, 2018), and contribute to the nucleation and growth of secondary aerosol (e.g., nitrate, sulfate, SOA) by partitioning between gas and particle phases (Foreman et al, 2016;Vereecken, 2017;Huang et al, 2014Huang et al, , 2015Ji et al, 2017;Xu et al, 2014). The bimolecular processes of SCIs at the air-water interface have been extensively studied both experimentally and theoretically (Zhu et al, 2016;Kumar et al, 2017Kumar et al, , 2018Zhong et al, 2017Zhong et al, , 2018Enami and Colussi, 2017;Heine et al, 2017), and the reaction with atmosphereabundant water vapor in the gas phase or at the air-water interface has been identified as one of the dominant degradation pathways of SCI removal from the atmosphere (Taatjes et al, 2013;Chen et al, 2016a, b;Lin et al, 2016;Huang et al, 2015;…”
Section: Introductionmentioning
confidence: 99%
“…200 This will lower the product yields at high relative humidity of secondary ozonides and hydroperoxide esters and increase the formation of volatile carbonyls relative to their yields under dry conditions. 177,201 In the aqueous phase, a-hydroxyhydroperoxides decompose to carbonyls and hydrogen peroxide, 202 but whether this occurs on surfaces under sub-saturated conditions is not known. Despite affecting the product distributions, enhanced relative humidity has no effect on the loss rate of ozone with unsaturated oils, such as oleic acid, triolein and squalene.…”
Section: (C) Multiphase Reactionsmentioning
confidence: 99%
“…These authors used the kinetic multilayer model for aerosol surface and bulk chemistry (KM-SUB) to attribute this RH dependence on inhomogeneous mixing of reactants and products and calculated that at RH = 50%, the BSA diffusion coefficient was 10 À20 cm 2 s À1 with a viscosity close to that of a glass, 36 typically greater than 10 12 Pa s. [53][54][55] Ozone had a diffusion coefficient of 10 À9 cm 2 s À1 and was predicted only to be present and reacting in the first tens of nanometers of the BSA films. 36 Heine et al 41 found that the decay of squalene reacting with O 3 over time was identical over the RH range of 0-60%, leading them to use a stochastic multilayer model, Kinetiscope, to reproduce their results having a 1 nm adsorption layer where the reaction with O 3 was predicted to mainly occur. This was supported by the authors' previous studies 40 and their calculations of the O 3 diffusion coefficient during reaction observed for particles with a 1-2 nm squalene coating.…”
Section: Introductionmentioning
confidence: 99%